The impact of low-cost carriers on consumer travel behaviour. - Lim, Song Yee. (2011)
In recent years, the Asian aviation industry has seen a sudden influx of low-cost carriers mainly due to government deregulation. Consequently, this emergence of low-cost carriers has brought about a significant change in consumer travel behavior. As such, this study aims to identify the variables contributing to this shift and recognises its effects on the air travel industry.